ANTHROPOMETRIC DETERMINANTS OF ROWING ERGOMETER PERFORMANCE IN PHYSICALLY INACTIVE COLLEGIATE FEMALES - R Podstawski; DJ Choszcz; S Konopka; J Klimczak; M Starczewski (Termedia Publishing House, 2015)
The aim of the study was to evaluate anthropometric characteristics as determinants of 500 m rowing ergometer performance in physically inactive collegiate females. In this cross-sectional study, which included 196 collegiate females aged 19-23 years not participating in regular physical activities, body mass (BM), body height (BH), length of upper limbs (LA), length of lower limbs (LL), body mass index (BMI), slenderness index (SI), and the Choszcz-Podstawski index (CPI) were measured and a stepwise multiple regression analysis was performed. Participants performed 500 m maximal effort on a Concept II rowing ergometer. BM, BH, LA, LL, and the BMI, SI and CPI indices were found to be statistically significant determinants of 500 m performance. The best results (T) were achieved by females whose BH ranged from 170 to 180 cm, with LA and LL ranging from 75 to 80 cm and 85 to 90 cm, respectively. The best fitting statistical model was identified as: T = 11.6793 L R - 0.1130 L R 2 - 0.0589 L N 2 + 29.2157 CPI 2 + 0.1370 LR·LN - 2.6926 LR·CPI - 211.7796. This study supports a need for additional studies focusing on understanding the importance of anthropometric differences in rowing ergometer performance, which could lead to establishing a better quality reference for evaluation of cardiorespiratory fitness tested using a rowing ergometer in collegiate females